Bibliometric Analysis of Ethical Behavior in Education Using VOSviewer - Rais Hidayat; Yuyun Elizabeth Patras; Herlina Usman; Yusuf Gunawan; Tustiyana Windiyani (Yayasan Keluarga Guru Mandiri, 2023)
The research theme of ethical behavior, particularly in educational organizations, is of great importance. There have been many publications on ethical behavior, but there has been no research to identify and summarize publications on it comprehensively. This research aims to clarify the history and predict the hotspots of ethical behavior themes in the future. This research method uses bibliographical analysis using the VOSviewer application. Data was sourced from the Scopus database between 1982 and 2021, downloaded into Excel 2016, and processed by VOSviewer. Bibliometric maps are formed by VOSviewer software automatically.Results of the research, which began with a search on the article title through the keyword